Antagonistic interaction between central glucagon-like Peptide-1 and oxytocin on diet-induced obesity mice. Issue 10 (October 2020) - Lee, Jeonghoon; Moon, Haneul; Lee, Hyunji; Oh, Yunkyeong; Kim, Changyeon; Lee, Young Hee; Kim, Min Sun; NamKoong, Cherl; Lee, Hee Won; Kim, Jung Hee; Choi, Hyung Jin
Abstract: Glucagon-like peptide-1 (GLP-1), whose agonists are widely prescribed, is a peptide proven effective in reducing obesity. Similarly, oxytocin (OXT) is a peptide known to increase satiety and help reduce body weight. In the present study, we aimed to examine the metabolic effects of co-administration of GLP-1 and OXT in diet-induced obesity (DIO) mice to elucidate their functions and interactions in the central nervous system. To this end, 40 DIO mice were subjected to stereotaxic surgery for the installation of an osmotic minipump and intracerebroventricular administration of GLP-1, OXT, or both. Initially, it was anticipated that co-administration of these anorexigenic peptides would be as effective as, if not more than, either GLP-1 or OXT alone in providing metabolic benefits to the obese mice. Interestingly, co-administration of OXT and GLP-1 offset the reductions in body weight and food intake promoted by either peptide alone. Co-administration also negated the decrease in fat and increase in lean mass produced by either peptide alone. Moreover, co-administration showed an equivalent calorimetric benefit as either peptide alone. Therefore, these results suggest antagonistic, rather than synergistic or additive, effects of centrally administered GLP-1 and OXT that attenuate the metabolic benefits of either peptide. Abstract : Nervous system; Molecular neuroscience; Peptides; Diet; Metabolism; Glucagon-like peptide-1 (GLP-1); Oxytocin (OXT); Antagonism; Calorimetry; Obesity; Neuropeptides.